Strategy to Increase Tourists at Merdeka Beach, Serdang Bedagai, North Sumatra-Indonesia - Syahputra, Budi; Widodo, Slamet (Sinergi International Journal of Economics, 2023)
Merdeka Beach in Serdang Bedagai has great potential as a leading tourist destination, but its development still faces challenges, especially in providing infrastructure and facilities that are in accordance with local characteristics and tourist needs. In this context, this study aims to identify and analyze the need for infrastructure and facilities that can increase the number of tourists at Merdeka Beach, as well as evaluate the effectiveness of collaboration between the government, local communities, and the private sector in developing this destination sustainably. This study uses a qualitative approach that allows for in-depth exploration of the experiences and perceptions of managers and tourists, with data collection techniques including observation, interviews, and documentation, and supported by literature studies. The results of the study indicate that although there have been significant efforts to improve infrastructure and facilities, there are still gaps, especially in terms of accessibility and destination promotion. Collaboration between related parties has had a positive impact, but strengthening is still needed, especially in terms of marketing strategies and the development of more complete facilities to meet tourist expectations. This study contributes to the understanding of the importance of synergy between various parties in managing new tourist destinations in rural areas, and emphasizes the need for a holistic approach that integrates economic, social, and environmental aspects in tourism development.